2021
DOI: 10.3390/jcm10071478
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Neurorehabilitation: An Umbrella Review of Meta-Analyses

Abstract: Neurological disorders are a leading cause of death and disability worldwide. Can virtual reality (VR) based intervention, a novel technology-driven change of paradigm in rehabilitation, reduce impairments, activity limitations, and participation restrictions? This question is directly addressed here for the first time using an umbrella review that assessed the effectiveness and quality of evidence of VR interventions in the physical and cognitive rehabilitation of patients with stroke, traumatic brain injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 89 publications
1
53
0
2
Order By: Relevance
“…Eight studies assessed the effectiveness of virtual care in the general adult population. Five of the reviews demonstrated positive effects (Alashram et al, 2019;Betts et al, 2018;Bogdanova et al, 2016;Leopold et al, 2015;Voinescu, Sui, and Fraser, 2021), one found mixed effects (Manivannan et al, 2019), and two drew uncertain conclusions (Brassel et al, 2021;Buhagiar et al, 2020). Physical exercise was tested for cognitive effects in four systematic reviews.…”
Section: Cognitivementioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies assessed the effectiveness of virtual care in the general adult population. Five of the reviews demonstrated positive effects (Alashram et al, 2019;Betts et al, 2018;Bogdanova et al, 2016;Leopold et al, 2015;Voinescu, Sui, and Fraser, 2021), one found mixed effects (Manivannan et al, 2019), and two drew uncertain conclusions (Brassel et al, 2021;Buhagiar et al, 2020). Physical exercise was tested for cognitive effects in four systematic reviews.…”
Section: Cognitivementioning
confidence: 99%
“…Virtual care was tested in seven systematic reviews that assessed functional outcomes, all in the general adult population. Two demonstrated effectiveness (Leopold et al, 2015;Voinescu, Sui, and Fraser, 2021), one did not (Alashram et al, 2020), two had mixed findings (Ownsworth et al, 2018;Sigmundsdottir, Longley, and Tate, 2016), and two drew uncertain conclusions (Brassel et al, 2021;Postol et al, 2019). Physical exercise was assessed for its effect on functional outcomes in two systematic reviews examining the general adult population.…”
Section: Functionalmentioning
confidence: 99%
“…Different possibilities for the use of VR have shown positive results, and the use of available non-immersive virtual reality video game consoles to provide “exergames” (i.e., a mixture of physical activity presented within the structure and flow of a game, which can function as a form of physical exercise) have been considered interesting [ 11 , 12 ]. According to Voinescu et al, in individuals with CP, the use of VR is a positive rehabilitation technique that provides movement, physical activity, and engagement [ 13 ]. Moreover, VR can provide improvement in lower limb strength, static and dynamic balance, mobility, increased gait speed, and improved gross motor function of the participants [ 6 , 7 , 8 , 9 , 10 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the efficacy of VR therapies is still under debate. The existing literature reports mixed findings [2,11], with results often obtained from small groups and sometimes without an adequate control comparison. Thus, more research is needed to better understand the effects of VR-based rehabilitation on different clinical conditions.…”
Section: Introductionmentioning
confidence: 99%